The Implementation of The Dual Banking System and the Development of Sharia Banking in Indonesia: A Study on Bank Syariah Indonesia (BSI) - Husaeni, Firman; Sunaryo Mukhlas, Oyo (Zona Law And Public Administration Indonesia, 2025)
The banking system in Indonesia adopts a dual banking system, namely a conventional banking system and a sharia banking system that run side by side in the same regulation. The implementation of the dual banking system is regulated in Law Number 10 of 1998 concerning Banking and Law Number 21 of 2008 concerning Sharia Banking. The purpose of this system is to provide choices to the public in making transactions according to their preferences, both conventionally and according to sharia principles. However, in its implementation, the dual banking system raises various challenges that have an impact on the development of sharia banking in Indonesia. This study aims to analyze the implementation of the dual banking system on the development of sharia banking in Indonesia with a case study of Bank Syariah Indonesia (BSI). In addition, this study also evaluates the suitability of the implementation of the sharia banking system with Islamic law and the obstacles faced in its implementation. The results of this study are that the implementation of the dual banking system in Indonesia has positive and negative impacts on the development of sharia banking. On the one hand, this system provides flexibility for the public in choosing banking services according to their beliefs. However, on the other hand, this system also makes it difficult for Islamic banks to develop independently and is vulnerable to the influence of the conventional banking system